Analisis Kesalahan Siswa Kelas 5 SD dalam Menyelesaikan Soal Bangun Ruang di Yayasan Madrasah Islamiyah Sinaksak - Nadhira Eka Putri Prayudi; Nabila Mutiara Syifa; ⁠Putri Syahbilah; Syalwa Nur Alisya; Mirna Wulan Sari Sianipar; Fitrah Ifandi Hasibuan; Muhammad Amin Fauzi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the types of errors made by 5th grade elementary school students in solving spatial geometry problems and to identify the factors that cause them. The subjects of the study were 5th grade elementary school students at the Sinaksak Islamic Madrasah Foundation in the 2024/2025 academic year. Data were obtained through written tests and interviews with 15 students. The results of the study showed that the errors often made by students included conceptual errors (45%), procedural errors (32%), and computational errors (23%). Conceptual errors are mainly related to understanding the formulas for volume and surface area of spatial geometry, procedural errors are related to unsystematic solution steps, while computational errors are in the form of errors in making calculations. Factors that cause errors include weak conceptual understanding, difficulty in visualizing spatial geometry, and lack of practice questions. This study provides recommendations for improving students' conceptual understanding of spatial geometry through the use of concrete learning media and providing varied practice questions.